A novel T4- and λ-based receptor binding protein family for bacteriophage therapy host range engineering - Magaziner, Samuel J.; Salmond, George P. C. (Frontiers in Microbiology, 2022)
Widespread multidrug antimicrobial resistance in emerging pathogens has led to a renewed interest in phage therapy as an alternative or supplement to traditional small molecule drugs. The primary limiting factors of phage therapy deployment rest in the narrow host range specificity of phage as well as a poor understanding of many phages’ unintended downstream effects on host physiology and microbiota as well as on adverse pathogen evolution. Consequently, this has made assembling well-defined and safe “phage-cocktails” of solely naturally occurring phages labor- and time-intensive. To increase the speed, efficacy, and safety of therapeutic deployment, there is exceptional interest in modulating the host ranges of well-characterized lytic phages (e.g. T4, T7) by using synthetic strategies to the swap phage tail components, the receptor binding proteins (RBPs) key for host specificity. Here we identify the RBP of the Citrobacter rodentium temperate phage ΦNP as ORF6. Through bioinformatic and phylogenetic assays we demonstrate this RBP to be closely related to the known RBPs of T4 and λ. Further investigation reveals a novel, greater than 200 member RBP family with phages targeting several notable human pathogens, including Klebsiella pneumoniae, Escherichia coli O157:H7, Salmonella spp., and Shigella spp. With well characterized lytic members, this RBP family represents an ideal candidate for use in synthetic strategies for expanding therapeutic phage host ranges.